2021
DOI: 10.3389/fpsyt.2021.696827
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics as a Mechanism of Developmental Embodiment of Stress, Resilience, and Cardiometabolic Risk Across Generations of Latinx Immigrant Families

Abstract: Psychosocial stressors can become embodied to alter biology throughout the life course in ways that may have lasting health consequences. Immigrants are particularly vulnerable to high burdens of stress, which have heightened in the current sociopolitical climate. This study is an investigation of how immigration-related stress (IRS) may impact the cardiometabolic risk and epigenetic markers of Latinx immigrant mothers and children in Nashville, TN. We compared stress and resilience factors reported by Latina … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 80 publications
(105 reference statements)
0
4
0
Order By: Relevance
“…For instance, in Latin American immigrant mothers and children, the associations between social determinants of mental health and resilience factors, and targeted DNA methylation in the stress-related genes FKBP5 and SLCA4 were investigated in a study by Clausing and Non [ 65 ]. The study found an epigenetic pathway through which early adversity and ongoing stressful life events correlate with important regulatory regions of these two genes.…”
Section: Environmental Factors Acting Epigenetically In Psychiatric D...mentioning
confidence: 99%
“…For instance, in Latin American immigrant mothers and children, the associations between social determinants of mental health and resilience factors, and targeted DNA methylation in the stress-related genes FKBP5 and SLCA4 were investigated in a study by Clausing and Non [ 65 ]. The study found an epigenetic pathway through which early adversity and ongoing stressful life events correlate with important regulatory regions of these two genes.…”
Section: Environmental Factors Acting Epigenetically In Psychiatric D...mentioning
confidence: 99%
“…To our knowledge, there have been few studies of the link between differential DNAm and immigration-related stress. Two studies directly examining immigration-related stress demonstrated its association with epigenetic age [ 110 ] and differential DNAm at stress-related candidate genes, such as SLC6A4 [ 111 ]. Other studies indirectly addressing this topic compared immigrants with non-immigrants.…”
Section: Current State Of Dnam Research In the Context Of Race Ethnic...mentioning
confidence: 99%
“…In general, individuals who are better able to use varied and appropriate coping strategies tend to report lower levels of stress, emotional and physical distress (Cheng, 2001;Kato, 2012). In particular, various environmental and psychosocial factors have been reported to contribute to individual differences in migrant well-being (Clausing & Non, 2021;Fong et al, 2022;Levitt et al, 2005). However, little is known about how environmental and psychosocial factors interrelate to affect post-migration well-being.…”
Section: Migration Stress and Well-beingmentioning
confidence: 99%
“…However, there is variability in the effects of migration-related stressors on the wellness of migrants, as some appear to be resilient while others may find these stressors to be particularly challenging and difficult to overcome. There appear to be various biological, psychosocial, and environmental factors that likely contribute to individual differences in post-migration well-being (Clausing & Non, 2021;Fong et al, 2022;Levitt et al, 2005).…”
Section: General Introductionmentioning
confidence: 99%